Self-generated temperature gradient under uniform heating in p–i–n junction carbon nanotube thermoelectric generators - Oga Norimasa; Ryota Tamai; Hiroto Nakayama; Yoshiyuki Shinozaki; Masayuki Takashiri (Scientific Reports)
Abstract Single-walled carbon nanotubes (SWCNTs) have attracted attention for use in thermoelectric generators (TEGs) that convert thermal energy into electricity. SWCNTs, which are lightweight, flexible, and nontoxic materials, are perfectly suited for TEGs as self-contained power sources for Internet of Things (IoT) sensors. However, the generation of electricity by TEGs requires not only a heat source to create a temperature gradient within the TEGs but also a cold source. In this study, we prepared SWCNT-TEGs consisting of p–i–n junction SWCNT films on a polyimide sheet that automatically generated a temperature gradient within the SWCNT-TEGs by uniform heating without a cold source. The output voltage and current of the SWCNT-TEG increased with increasing temperature. At a heating temperature of 370 K, the SWCNT-TEG exhibited an output voltage of 2.3 mV, a short-circuit current of 13.7 µA, and a maximum output power of 7.7 nW. The self-generated temperature gradient under uniform heating was attributed to the higher optical absorption of the SWCNT film than that of the polyimide sheet, which increased the temperature of the SWCNT film. The results of this study indicate that a simple attachment of SWCNT-TEGs to a heat source can sustainably power an IoT sensor as self-contained power sources.